Primary Optic Nerve Sheath Meningioma with Choroidal Neovascular Membrane-A Rare Association - Dr. Anamika Tiwari, Dr. Eva Rani Tirkey, Dr. Neha Adlakha, (International Journal of Innovative Research in Medical Science, 2017)
Primary optic nerve sheath meningiomas (ONSMs) are rare tumors arising from meningoendothelial cells of anterior visual pathway and constitute approximately 2% of all orbital tumors and 1–2% of all meningiomas. A 25 year old male presented with painless diminution of vision and slowly progressive outward protrusion of right eye since 12 months. His visual acuity was 20/120 in right eye and 20/20 in left eye. Reaction to light was sluggish in right eye and relative afferent pupillary defect was present. Proptosis was 25 mm in right eye and 18 mm in left eye. On automated perimetry, right eye showed enlargement of blind spot while left eye was normal. On fundus examination, right eye showed marked optic nerve head swelling, venous dilatation, tortousity along with extensive superficial and deep haemorrhages and a hypopigmented lesion superiorly around half disc diameter from optic disc. Fundus flouroscein angiography showed disc hyperflourescence, hypoflourescence due to haemorrhages and hypoflourescence in a lesion superior to optic disc with late leakage, suggestive of scarred CNVM. Contrast enhanced CT scan orbit showed tram track appearance of right optic nerve suggestive of right primary optic nerve sheath meningioma. Systemic examination revealed no other evidence of neurofibromatosis and there was no family history of hearing loss or central nervous system tumours. Thyroid hormones were within normal limits. Definitive treatment of primary ONSMs is challenging. Surgical excision has almost always result in blindness in affected eye. This could be due to excision of tumor along with affected optic nerve intraoperatively or damage to pial vasculature. Conservative management is indicated if there is no significant progressive visual dysfunction or intracranial extension of tumor.